Opportunity Recognition: Gender and Family Business Background Comparison - Christina -; Maureen Nuradhi; Lili Kristanti (International Journal of Family Business Practices, 2021)
Opportunity recognition is the first nascent step towards entrepreneurship. Previous study shows that gender and family business exposure plays a significant role for entrepreneurs to start a business.  The objective of this study is to find out if there is any difference in opportunity recognition based on gender and family business background. The sample size of this study is 413 students who are taking the Entrepreneurial Global Innovation subject in the fourth semester at Universitas Ciputra Surabaya, comprising 234 males and 179 females. The data was taken at the end of the semester which also coincided with the pandemic covid-19 situation. The data that has been collected is analyzed using independent sample t-test. The result of the study reveals that there is a difference in opportunity recognition between students with family business backgrounds and students without family business background. The other result of this study is that there is no difference in opportunity recognition between male and female.This study contributes to entrepreneurship education especially in term of opportunity recognition and how it is differ between students who have family business background and those who don’t. Further research needs to be done to ascertain whether gender equality in entrepreneurship has actually been achieved.